ABA triblock copolyesters composed of poly(l-lactide) A hard blocks: A comparative study of amorphous and crystalline aliphatic polyesters as B soft blocks. (March 2020) - Wei, Zhiyong; Che, Rui; Shao, Shengnan; Wang, Yanshai; Leng, Xuefei; Li, Yang
Abstract: In this article, two series of ABA triblock copolyesters composed of poly(l -lactide) A hard blocks and odd-odd aliphatic polyesters as B soft midblock were prepared and compared by various techniques. The results showed that the block structures could be formed without any detectable transesterification, and the composition and molecular weight of the triblock copolyesters could be well controlled by adjusting the feeding ratio of l -lactide monomer to the polyester macroinitiator. It was found that the thermal properties, crystal structure, and spherulitic morphology of the triblock copolyesters depended on the composition and block length. The impact of amorphous and crystalline midblocks on the mechanical properties was compared and discussed. The triblock copolyesters composed of crystalline midblock showed similar ultimate stress and elongation, but higher tensile modulus and yield stress, in comparison with analogous containing amorphous midblock. The triblock copolyester composed of short PLLA hard block and amorphous aliphatic polyester soft midblock displayed typical elastomeric behavior without yield, which is a promising aliphatic polyester thermoplastic elastomer. Graphical abstract: Image 1 Highlights: Aliphatic polyester thermoplastic elastomers have been successfully synthesized. Aliphatic polyesters were used as B soft midblock of PLLA triblock copolymers. Impact of amorphous and crystalline midblocks on the mechanical properties has been compared. The elongation at break up to 676% illustrates well toughening modification.